Batch Studies of Zinc(II) Ion Adsorption onto Alginic Acid Fibres - Qingshan Kong; Chunxiang Guo; Fangfang Cheng; Quan Ji; Yanhui Li; Yanzhi Xia (Adsorption Science & Technology, 2010)
The ability of alginic acid fibres to remove Zn(II) ions from aqueous solution was investigated by batch experiments. The effect of experimental parameters including pH, agitation time, initial Zn(II) ion concentration, temperature and biosorbent dosage on the biosorption of Zn(II) ions from aqueous solution was studied. Thermodynamic studies of Zn(II) ion biosorption demonstrated the exothermic nature of the process. Kinetic studies showed that the biosorption conformed to the pseudo-second-order and intra-particle diffusion models. The Langmuir and Freundlich isotherm models provided a good fit to the experimental data. The activation energy for the biosorption process suggested that it occurred in a physical manner. Alginic acid fibres have been demonstrated to be effective marine materials for the removal of Zn(II) ions from aqueous solution.